2022
DOI: 10.1007/s40266-022-00942-1
|View full text |Cite
|
Sign up to set email alerts
|

Depression in Patients with Parkinson’s Disease: Current Understanding of its Neurobiology and Implications for Treatment

Abstract: Depression is one of the most frequent and burdensome non-motor symptoms in Parkinson's disease (PD), across all stages. Even when its severity is mild, PD depression has a great impact on quality of life for these patients and their caregivers. Accordingly, accurate diagnosis, supported by validated scales, identification of risk factors, and recognition of motor and non-motor symptoms comorbid to depression are critical to understanding the neurobiology of depression, which in turn determines the effectivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 316 publications
0
39
0
3
Order By: Relevance
“…Even though a unified pathophysiological model of depression in PD, considering the interaction with incidental depression after diagnosis, is still lacking [5], its onset may precede the motor manifestations [6] and affects patients' overall prognosis [7].…”
Section: Introductionmentioning
confidence: 99%
“…Even though a unified pathophysiological model of depression in PD, considering the interaction with incidental depression after diagnosis, is still lacking [5], its onset may precede the motor manifestations [6] and affects patients' overall prognosis [7].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with PD experience non-motor symptoms related to the accumulation of α-syn and the loss of dopaminergic and noradrenergic innervations in certain brain regions (among which LC stands out) and in some regions of the limbic system, and the main repercussions involve neuropsychiatric or autonomic dysfunctions [ 78 , 82 , 84 ]. The most frequent are depression [ 85 , 86 ], anxiety [ 86 ], fatigue and sleep disorders [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, modern in vivo imaging studies demonstrated that DPD is mainly underpinned by dysfunction of basal ganglia-cortico-limbic networks and monoaminergic systems, depending on the stage of PD and associated symptoms, including autonomic dysfunctions, CI, and RBD. In particular, the evolution of dopaminergic and serotonergic dysfunction and abnormalities of limbic circuits across time, involving the orbitofrontal and anterior cingulate cortices, ventral striatum, amygdala, thalamus, and other important brain networks, help to delineate the variable expression and severity of depression in patients with preclinical/prodromal, early and advances stages of PD (Prange et al 2022 ). A history of depression may also be an increased risk of adverse effects following subthalamic nucleus deep brain stimulation (Kratter et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these data suggest that depression and PD may share common pathophysiological mechanisms, although these are multifactorial and complex, related to a variety of pathobiological mechanisms associated with the underlying neurodegenerative process of PD (Jankovic and Tan 2020 ; Prange et al 2022 ; Weintraub et al 2022 ), the essential ones will be critically reviewed.…”
Section: Depression In Genetic Pdmentioning
confidence: 99%
See 1 more Smart Citation